2014
DOI: 10.1097/sla.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Arm, Nonrandomized Phase II Trial of Neoadjuvant Gemcitabine and Oxaliplatin in Patients With Resectable Pancreas Adenocarcinoma

Abstract: Objective The role for neoadjuvant systemic therapy in resectable pancreas adenocarcinoma remains undefined. We evaluated the efficacy of gemcitabine and oxaliplatin administered as preoperative therapy in patients with resectable pancreas adenocarcinoma. Methods Eligible patients were screened using CT pancreas angiography, laparoscopy, endoscopic ultrasound and fine needle aspiration cytology, to identify 38 patients who received four cycles of neoadjuvant gemcitabine 1000mg/m2 IV over 100 minutes and oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
109
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 36 publications
2
109
0
1
Order By: Relevance
“…100,[157][158][159] Well established ICD inducers include commonly employed anticancer chemotherapeutics such as: (1) (6) bortezomib, a proteasomal inhibitor approved for the therapy MM and mantle cell lymphoma (MCL); [171][172][173][174][175][176][177][178][179][180][181] (7) cyclophosphamide, a DNA-alkylating agent approved for use in patients with chronic myeloid leukemia (CML), AML, ALL, chronic lymphocytic leukemia, MM, ovarian carcinoma, breast carcinoma, mycosis fungoides, lymphoma, neuroblastoma, and retinoblastoma; 177,[182][183][184][185][186][187][188][189][190][191] and (8) oxaliplatin, a platinum-derivative licensed for the therapy of advanced colorectal carcinoma in combination with 5-fluorouracil and folinic acid. 156,157,[192][193][194][195][196][197][198] Moreover, there is some evidence that microtubule-targeting agents including taxanes and vinca alkaloids (which are commonly used for the treatment of multiple carcinomas) can stimulate ICD. 41,199 Along the lines of our Trial Watch series, here we discuss recent preclinical and clinical advances in the development of ICD-inducing chemotherapeutic regimens.…”
Section: Introductionmentioning
confidence: 99%
“…100,[157][158][159] Well established ICD inducers include commonly employed anticancer chemotherapeutics such as: (1) (6) bortezomib, a proteasomal inhibitor approved for the therapy MM and mantle cell lymphoma (MCL); [171][172][173][174][175][176][177][178][179][180][181] (7) cyclophosphamide, a DNA-alkylating agent approved for use in patients with chronic myeloid leukemia (CML), AML, ALL, chronic lymphocytic leukemia, MM, ovarian carcinoma, breast carcinoma, mycosis fungoides, lymphoma, neuroblastoma, and retinoblastoma; 177,[182][183][184][185][186][187][188][189][190][191] and (8) oxaliplatin, a platinum-derivative licensed for the therapy of advanced colorectal carcinoma in combination with 5-fluorouracil and folinic acid. 156,157,[192][193][194][195][196][197][198] Moreover, there is some evidence that microtubule-targeting agents including taxanes and vinca alkaloids (which are commonly used for the treatment of multiple carcinomas) can stimulate ICD. 41,199 Along the lines of our Trial Watch series, here we discuss recent preclinical and clinical advances in the development of ICD-inducing chemotherapeutic regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of a 20% ORR (without radiation) and a 29% ORR with selective radiation therapy are similar, and suggest that response to FOLFIRINOX may be superior to other reported regimens. The above ORRs display a consistent pattern, in which the ORR with FOLFIRINOX is at least two-fold higher compared to non-FOLFIRINOX regimens 1,4 . It should be noted however, that a high ORR(23%) was recently reported in stage IV PDAC patients in a phase III randomized trial that evaluated a novel regimen of nab-paclitaxel plus gemcitabine 21 .…”
Section: Discussionmentioning
confidence: 81%
“…Retrospective studies of patients with both borderline resectable PDAC (stage I-II) and stage III patients(locally unresectable) have also suggested an ORR of approximately 30% with FOLFIRINOX 2,3 . The reported ORR from non-FOLFIRINOX regimens has generally been in the range of 10%, including the results of a phase II study from our institution that demonstrated a 10% ORR for resectable patients treated with preoperative gemcitabine and oxaliplatin therapy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41] Among those who underwent resection, 69% to 83% had R0 resection. No complete response was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Another report 40 testing GemOx in 27 resected patients noted no mortality; benign fluid collections and infections were present in 2 (7.4%) patients each, with 1 patient each (3.7%) experiencing anastomotic leak, bowel perforation, and hemorrhage.…”
Section: Complications After Neoadjuvant Chemotherapymentioning
confidence: 96%